Breaking down silos: On post-harvest loss interventions in Tanzania - Vandercasteelen, Joachim; Christiaensen, Luc (LICOS Centre for Institutions and Economic Performance, 2020)
Post-Harvest Losses (PHL) are considered to pose important economic losses for farmers in developing countries. This paper examines the effects of an intervention in Tanzania, aimed at reducing PHL of maize growing farmers during maize storage. Farmers were invited to attend a training on best practices in postharvest maize management, and a randomized subset of trainees received the opportunity to buy an improved storage facility (silos) at a substantially discounted price. Data collected at 30 days and 90 days after harvest, however, do not point to significant impacts of the treatments offered to the farmers. Receiving training on best practices improved stated knowledge, but training nor the opportunity to purchase an improved storage had a significant effect on maize storage and sales behavior, physical PHL during storage, or the quality of the stored maize. The paper explores potential explanations, and provides some policy recommendations for future learning and decision-making on how to address PHL issues in developing countries.